Pengaruh Peningkatan Jasa Pelayanan Medis erhadap Jumlah Rujukan Pasienrawat Inap Di Rsud Syamsudin SH, Sukabumi - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 1997)
ABSTRACT This time-serie quasi experimental study aims to assess whether the change of fee payment mechanism may improve doctors motivation to increase the number of their inpatient referral at Syamsudin SH Hospital, Sukabumi. The specific objectives of this study are: (1) which distribution of fee-for-service that may satisfy the doctors so they can be more motivated to increase the number of in-patient referral